Prolonged Pyrexia due to Hemophaghocytic Lymphohistiocytosis (Bangladesh Critical Care Journal, 2015)
Haemophaghocytic lymphohistiocytosis (HLH) is an uncommon illness in adults. It is rare but common clinical features like lymphadenopathy, hepatosplenomegaly, fever are presentation of many different familiar clinical illness, make it a diagnostic challenge. Here, we present a case of a previously healthy young boy presented with fever and other features like hepatosplenomegaly, pancytopenia, markedly elevated serum ferritin, Lactate dehydrogenase, triglyceride, low fibrinogen, persistent hyponatremia and finally detectable Haemophagocytosis in his bone marrow. Unfortunately, diagnosis was delayed around 4 month after his initial presentation and he succumbed to his disease. This case highlights common clinical features and diagnostic difficulties have to face in making confirmed diagnosis of HLH.Bangladesh Crit Care J September 2015; 3 (2): 77-78